Angiogenic factors for planning fetal surveillance in fetal growth restriction and small‐for‐gestational‐age fetuses: A prospective observational study. (5th April 2022) - Bonacina, Erika; Mendoza, Manel; Farràs, Alba; Garcia‐Manau, Pablo; Serrano, Berta; Hurtado, Ivan; Ferrer‐Oliveras, Raquel; Illan, Lidia; Armengol‐Alsina, Mireia; Carreras, Elena
Abstract: Objective: The aim of this study was to assess the added value of the soluble fms‐like tyrosine kinase‐1 (sFlt‐1) and placental growth factor (PlGF) ratio for adjusting the periodicity of ultrasound examinations in early‐onset fetal growth restriction (FGR) and small for gestational age (SGA). Design: A prospective, observational study. Setting: Tertiary referral hospital. Population: One hundred and thirty‐four single pregnancies with ultrasonographic estimated fetal weight (EFW) below the 10th centile between 20 +0 and 31 +6 weeks of gestation with antegrade umbilical artery flow. Methods: The time from Doppler and sFlt‐1/PlGF assessment to delivery was recorded and classified into four ranges: <1, <2, <3 and <4 weeks. Main outcome measures: Sensitivity (Sn), specificity (Sp), positive predictive value (PPV) and negative predictive value (NPV) of sFlt‐1/PlGF values to predict the time to delivery. Results: In the SGA cohort, the NPV calculated for an sFlt‐1/PlGF cut‐off value of 38 was 100% for delivery before 3 weeks, and 98% for delivery before 4 weeks after diagnosis (95% CI 0.89–1.00). In the FGR cohort, the NPV calculated for an sFlt‐1/PlGF cut‐off value of 38 was 100% for delivery before 2 weeks after diagnosis (95% CI 0.92–1.00). By contrast, more than 50% of cases with an sFlt‐1/PlGF value of >85 required an elective delivery before 1 week. Conclusions: sFlt‐1/PlGF values in early‐onset SGA and FGR are predictive of the time to delivery and could be used for planning fetal surveillance, by reducing the frequency of ultrasound in cases with sFlt‐1/PlGF < 38 and by providing closer follow‐up in cases with sFlt‐1/PlGF >85. Tweetable abstract: sFlt‐1/PlGF values in early‐onset SGA/FGR could be used in addition to Doppler for planning fetal surveillance. Tweetable abstract: sFlt‐1/PlGF values in early‐onset SGA/FGR could be used in addition to Doppler for planning fetal surveillance. Linked article : This article is commented on by Cecilia Villalaín, pp. 1878 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471‐0528.17172